ISBAT NIKAH MUALLAF DALAM KONTEKS PLURALISME (ANALISIS PUTUSAN NOMOR 0062/PDT.P/2016/PA.JR) - Iswandi, Misbahuddin & Ilham (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2020)
Judge's Decision Number 0062/Pdt.P/2016.Jr contains a discussion about the determination of muallaf marriage. The marriage procession was initially carried out in a Catholic way and was recorded at the Civil Registry Office, after the passage of time the husband chose to convert to Islam and wanted to have an official marriage book with the law. applicable, then submit a request for marriage Isbat to the Jember Religious court then the decision was issued. The purpose of this study is to describe judges' considerations, review Islamic law and analyze the determination of judges in case Number 0062/Pdt.P/2016/PA.Jr in the context of pluralism. The method in this study, using qualitative methods with a Normative Juridical approach. The results of this study are the first Isbat Marriage Marriage or different religious marriages according to the law that has been regulated in regulations Number 1 of 1974 Regarding marriage and ratified on the basis of the Law of Mixed Marriage Ordination Stb. 1898 Number 158. Second According to Islamic law interfaith marriages are permissible if certain conditions are adjusted to the existing provisions and adhere to the shari'ah that has been believed. Third, according to the view of pluralism of different marriages. Religion shows the attitude of tolerance in this plural society.